2006
DOI: 10.1007/s00213-006-0586-x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of nicotine dose estimates in smokers between filter analysis, salivary cotinine, and urinary excretion of nicotine metabolites

Abstract: Rationale Nicotine uptake during smoking was estimated by either analyzing the metabolites of nicotine in various body fluids or by analyzing filters from smoked cigarettes. However, no comparison of the filter analysis method with body fluid analysis methods has been published. Objectives Correlate nicotine uptake estimates between filter analysis, salivary cotinine, and urinary excretion of selected nicotine metabolites to determine the suitability of these methods in estimating nicotine absorption in smoker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 22 publications
2
35
0
Order By: Relevance
“…NNAL and its metabolite were analyzed using a solid phase extraction and liquid [11] and Pan et al [12] (LLOQ 5ng/ml ULOQ 1000ng/ml). Urinary nicotine and its metabolites were analyzed using a solid phase extraction and liquid chromatography with tandem mass spectrometry as described by St. Charles et al [6] (LLOQ 10ng/ml ULOQ 5000ng/ml). When described below, total nicotine metabolites represent the sum of the nicotine, cotinine and hydroxycotinine plus all of their glucuronide conjugates, allowing for the molecular mass of the analyte, expressed as a mass of the parent molecule.…”
Section: Materials and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…NNAL and its metabolite were analyzed using a solid phase extraction and liquid [11] and Pan et al [12] (LLOQ 5ng/ml ULOQ 1000ng/ml). Urinary nicotine and its metabolites were analyzed using a solid phase extraction and liquid chromatography with tandem mass spectrometry as described by St. Charles et al [6] (LLOQ 10ng/ml ULOQ 5000ng/ml). When described below, total nicotine metabolites represent the sum of the nicotine, cotinine and hydroxycotinine plus all of their glucuronide conjugates, allowing for the molecular mass of the analyte, expressed as a mass of the parent molecule.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…In other studies with large numbers of subjects, a technique based on the analysis of smoked cigarette filters has been developed [6]. This method has the advantage of giving an estimate of mouth-level exposure for the cigarette actually smoked by each smoker without the need for the collection of any biofluid; however, it does not measure the amount of smoke drawn into the lungs or subsequently distributed throughout body tissues and so *Address correspondence to this author at the British American Tobacco, GR&D Regents Park Road, Southampton, SO15 8TL, UK; Tel: +44 (0)2380 793647; Fax: +44 (0)2380 793076; E-mail: Frazer_Lowe@bat.com interest has focused on the potential of biomarkers for this use [7].…”
Section: Introductionmentioning
confidence: 99%
“…The nicotine content in a 10-mm portion of the mouth end of the cigarette filter (26) and the cigarette butt length were determined from cigarette butts collected during the 24-hour urine collection period.…”
Section: Cigarette Butt Analysismentioning
confidence: 99%
“…Nicotine equivalents (NE) is the molar sum of nicotine measured in 24 h urinary excretion of nicotine and its five major metabolites (cotinine and cotinine-N-glucuronide, trans-3 0 -hydroxycotinine and trans-3 0 -hydroxycotinine-O-glucuronide, and nicotine-N-glucuronide) (Benowitz et al, 1994;Roethig et al, 2005;Scherer et al, 2007). It has been reported that 24 h urinary excretion of NE accounts for an average of about 80-90% of the systemic nicotine intake from smoking or from a nicotine patch (Benowitz et al, 1994;Feng et al, 2007;St Charles et al, 2006). Nicotine equivalents has been widely used as a biomarker for exposure to tobacco and cigarette smoke (Frost-Pineda et al, 2008a, 2008bMendes et al, 2008;Roethig et al, 2005Roethig et al, , 2007Roethig et al, , 2008Roethig et al, , 2009Sarkar et al, 2008;Shepperd et al, 2009;St Charles et al, 2006;Stratton et al, 2000;Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 96%